Engineering and comparison of non‐natural pathways for microbial phenol production. Issue 8 (4th February 2016) - Thompson, Brian; Machas, Michael; Nielsen, David R.
ABSTRACT: The non‐renewable petrochemical phenol is used as a precursor to produce numerous fine and commodity chemicals, including various pharmaceuticals and phenolic resins. Microbial phenol biosynthesis has previously been established, stemming from endogenous tyrosine via tyrosine phenol lyase (TPL). TPL, however, suffers from feedback inhibition and equilibrium limitations, both of which contribute to reduced flux through the overall pathway. To address these limitations, two novel and non‐natural phenol biosynthesis pathways, both stemming instead from chorismate, were constructed and comparatively evaluated. The first proceeds to phenol in one heterologous step via the intermediate p ‐hydroxybenzoic acid, while the second involves two heterologous steps and the associated intermediates isochorismate and salicylate. Maximum phenol titers achieved via these two alternative pathways reached as high as 377 ± 14 and 259 ± 31 mg/L in batch shake flask cultures, respectively. In contrast, under analogous conditions, phenol production via the established TPL‐dependent route reached 377 ± 23 mg/L, which approaches the maximum achievable output reported to date under batch conditions. Additional strain development and optimization of relevant culture conditions with respect to each individual pathway is ultimately expected to result in further improved phenol production. Biotechnol. Bioeng. 2016;113: 1745–1754. © 2016 Wiley Periodicals, Inc. Abstract : The authors systematically engineered two novel phenol biosynthesis pathways stemming from endogenous chorismate for comparison to the established route. Maximum titers from glucose reached 377 mg/L at a yield of 35.7 mg/g.